Wzorce postkomunistycznej transformacji. Artykuł recenzyjny - Brzechczyn, Krzysztof (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2014)
The paper presents and discusses main tenets of book authored Zenonas Norkus, On Baltic Slovenia and Adriatic Lithuania. A Qualitative Comparative Analysis of Patterns in Post-Communist Transformation. The Author of the paper focuses of comparative methodology applied in the reviewed book and obtained effects: identification of factors influencing transformation in Baltic stated after 1989.
Models of post-communist transformation. A review